Gender Differences in Students Misconceptions on Exponentiation Concepts: Perbedaan Gender dalam Miskonsepsi Siswa pada Konsep Bilangan Berpangkat - Zilfikri, Muhammad; Kamid, Kamid ⁠; Anggereini, Evita (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Misconceptions represent a fundamental issue in mathematics learning that can hinder students’ understanding of advanced concepts, particularly in exponentiation. Specific Background Students frequently experience conceptual errors in exponentiation, including generalization, notation, specialization, and mathematical language, which remain undetected due to limited use of diagnostic assessment. Knowledge Gap Previous practices have not sufficiently applied four-tier diagnostic tests combined with Certainty of Response Index to deeply identify misconceptions and their variation based on gender. Aims This study aims to describe students’ misconceptions in exponentiation concepts through conceptual understanding using a four-tier diagnostic test based on gender. Results The findings revealed that 23 out of 38 students experienced misconceptions, with a higher proportion among male students, characterized by dominance in generalization and symbolic notation errors, while female students tended to show misconceptions in language and conceptual application. Novelty The novelty lies in integrating a four-tier diagnostic test with CRI to uncover misconception characteristics and differentiate cognitive patterns between male and female students in exponentiation material. Implications These results indicate the necessity of gender-adaptive instructional strategies and periodic diagnostic assessment to identify misconceptions and design targeted learning interventions for improving conceptual understanding. HIGHLIGHTS • Higher misconception proportion observed among male learners compared to female learners• Distinct cognitive patterns identified between symbolic reasoning and language-based understanding• Diagnostic assessment reveals varied categories of conceptual misunderstanding KEYWORDS Misconceptions; Exponentiation; Four-Tier Diagnostic Test; Conceptual Understanding; Gender